2018
DOI: 10.1002/mop.31158
|View full text |Cite
|
Sign up to set email alerts
|

Design of a textile antenna with artificial magnetic conductor for wearable applications

Abstract: With the development of modern wireless technologies and the miniaturization of antennas and electrical systems, the use of antennas on the human body for Wi‐Fi applications has become important. However, integrating the antenna near the body immediately raises the question about the protection of the body and the radiation effectiveness of the antenna. One solution that has recently attracted great attention is the use of high impedance surfaces (HIS), which is studied here for the antennas integrated on clot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 12 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…Physical dimension comparison in terms of wavelength at the lowest operating frequency with antennas in the literature indicated that the proposed antenna featured a more compact size relative to [27] and [29]. Besides that, the gain obtained by the proposed antenna is also improved compared with those presented in [27], [28], [29], [30], and [31] at 5.8 GHz. Moreover, the obtained FBR in this work is also improved compared with [28] and [29].…”
Section: Design 3: Crown-shaped Patch With Amc Planementioning
confidence: 80%
“…Physical dimension comparison in terms of wavelength at the lowest operating frequency with antennas in the literature indicated that the proposed antenna featured a more compact size relative to [27] and [29]. Besides that, the gain obtained by the proposed antenna is also improved compared with those presented in [27], [28], [29], [30], and [31] at 5.8 GHz. Moreover, the obtained FBR in this work is also improved compared with [28] and [29].…”
Section: Design 3: Crown-shaped Patch With Amc Planementioning
confidence: 80%
“…Based on the works of Italian National Research Council the electrical properties of the tissues at three different resonance frequencies i.e. 3, 5, and 10 GHz are given in Table 3, which are easily available online [23]. To show the effect of human body on the proposed antenna parameters, an inhomogeneous three-layered body model containing skin, fat, and muscle is simulated in computer simulation technology microwave studio (CST MWS) version 16.0.…”
Section: Study Of Uwb and Integrated Wearable Antennasmentioning
confidence: 99%
“…The proposed integrated antenna has an optimum size of 50 × 44.4 mm 2 , largest operating bandwidth of 13.7 GHz and gain of 8 dB. Further, the radiation efficiency is not considered in most of the papers except [7, 14, 23, 24], whereas the proposed antenna gave comparatively highest radiation efficiency of 85%. Therefore, we can say that the designed antenna gave optimum and quite satisfactory results and can be considered as a good candidate for wearable applications.…”
Section: Study Of Uwb and Integrated Wearable Antennasmentioning
confidence: 99%
“…Finally, an EBG can be grouped in terms of design configuration such as Mushroom and uniplanar configuration 10,12 . The commonly designed EBG is a single band with a 2‐D configuration 8,10,13–16 . Dual‐band EBGs have been proposed in the literature such as Refs.…”
Section: Introductionmentioning
confidence: 99%
“…10,12 The commonly designed EBG is a single band with a 2-D configuration. 8,10,[13][14][15][16] Dual-band EBGs have been proposed in the literature such as Refs. 17-19.…”
mentioning
confidence: 99%